Adaptive preferences and women's empowerment - Khader, Serene J. (New York : Oxford University Press, 2011)
Khader offers a deliberative perfectionist approach to identifying and responding to adaptive preferences - deprived people's preferences that perpetuate their deprivation.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: Well-being -- Social aspects; Well-being -- Psychological aspects; Preferences (Philosophy); Oppression (Psychology); Choice (Psychology); Women -- Developing countries -- Social conditions; Feminism